Pengaruh Transparansi, Akuntabilitas, Pembangunan Desa, Dan Kepentingan Politik Terhadap Pengelolaan Alokasi Dana Desa (Studi pada Desa di Kabupaten Ponorogo Jawa Timur): A Study on Villages in Ponorogo Regency of East Java - Sulthoni, Ghulam Ihda; Amirya, Mirna (Universitas Pendidikan Ganesha, 2024)
This research evaluates the influence of transparency, accountability, village development, and political interest on Village Fund Allocations (ADD) management by village governments, addressing community concerns about fund usage. Using a quantitative approach with multiple linear regression, data from 100 villagers in four Ponorogo Regency villages, East Java, were analyzed. Results indicate that transparency, accountability, and village development positively impact ADD management, while political interest has a negative effect, highlighting potential challenges associated with political influences on fund management. However, the study has limitations, such as a small sample size and a focus on a specific regency, limiting generalizability. Recommendations include conducting future research with larger, more diverse samples for broader insights. Practical implications suggest implementing policies and practices to enhance transparency, accountability, and village development for effective fund utilization. Additionally, awareness of the negative impact of political interest underscores the need for measures to mitigate undue political involvement in fund management.